RECONFIGURING SHARIAH ECONOMIC LEGALITY: A NORMATIVE–JURIDICAL ANALYSIS OF ISLAMIC FINANCIAL GOVERNANCE - Amin Zaki; Ahmed Al Fahad; Sarah Williams (Yayasan Adra Karima Hubbi, 2026)
Islamic finance has expanded rapidly within diverse regulatory environments, raising critical questions about how Shariah economic legality is constructed and maintained. Legal interpretations in this field are shaped not only by formal compliance mechanisms but also by normative jurisprudence, institutional arrangements, and market dynamics, creating a complex and often fragmented governance landscape. This study aims to examine how Shariah legality is configured and to propose a reconfigurative framework that integrates normative and juridical perspectives within Islamic financial governance. A qualitative normative–juridical research design is employed through systematic analysis of 85 legal documents, including fatwas, regulatory frameworks, and international standards across multiple jurisdictions. Analytical matrices and coding techniques are used to identify patterns of legal reasoning, institutional structures, and interpretive authority. The findings reveal that centralized governance systems enhance consistency and innovation, while decentralized systems preserve interpretive diversity but increase legal fragmentation. Compliance-based standardization improves procedural clarity yet fails to eliminate epistemological divergence. These results indicate that Shariah economic legality is a dynamic construct shaped by continuous negotiation between doctrinal principles and institutional practices. The study concludes that effective Islamic financial governance requires integrative models that balance normative integrity with regulatory functionality, supporting both coherence and adaptability in a rapidly evolving financial environment.